THE USE OF TELL-SHOW COMBINED WITH PICTURE TO IMPROVE WRITING SKILL OF THE TENTH-GRADE STUDENTS OF SMKN 1 SUSUT - Komang Ary Trisna Wahyuni; I Komang Budiarta; Anak Agung Putri Maharani (Academic Journal on English Studies (AJOES), 2021)
The present study aimed at figuring out whether writing skill of the tenth-grade students of SMKN 1 Susut can be improved through the implementation of tell-show combined with picture. Tell-show was a teaching technique of writing in this study in which the subjects used writing columns during the online learning. The research was primarily based on the preliminary study of 26 tenth-grade students of SMKN 1 Susut in academic year 2020/2021. The research design was classroom action research, and the research was carried out through applying tell-show combined with picture within two cycles. Furthermore, the obtained data were collected by administering tests (pre-test and post-tests) and a questionnaire. The results showed that there was a significant improvement of the subjects’ descriptive text writing ability. The questionnaire also proved that the subjects’ responses toward the implementation of tell-show combined with picture were positive during the online class. In short, the present study clearly showed that writing skill of the tenth-grade students of SMKN 1 Susut in academic year 2020/2021 can be improved through tell-show combined with picture.